Using faunal remains from Bolt’s Farm Cave System (Cradle of Humankind) to understand the system’s palaeo-environment. - (:unkn) unknown (My University, 2023)
The Plio-Pleistocene sites of the Cradle of Humankind (UNESCO site), at Taung and Makapansgat Limeworks, all in South Africa, have yielded a rich collection of macrofauna and an abundance of microfauna. This has been validated by different publications on bovids, primates, carnivores, rodents, insectivores, elephant shrews and birds. The palaeokarst system of Bolt's Farm, Gauteng Province, South Africa, is no different from the above as it is endowed with numerous fossiliferous Plio-Pleistocene deposits. Macrofauna gives information about the past environment at the regional scale because of their high migration capacity. But ecosystems are often complex, mosaic, and to obtain a more precise reconstruction of the past environment, local indications must be considered. This information may concern the entire Cradle of Humankind, the nearby valley or only the site surroundings. Bovid faunal remains are useful in palaeo-ecological interpretations and elucidate contemporary regional environments. Carnivores on the other hand indicate prey size preferences and availability. Microfauna gives information about the local environmental conditions as they do not travel long distances. Fossils such as rodents, Mylomygale, Agama sp., Hemachatus haemachatus, and Geronticus cf. calvus have been yielded from Bolt's Farm Cave System and these have also been useful in the reconstruction of the palaeo-environment of the locality.
Keywords: African Research